2019
DOI: 10.18388/abp.2019_2886
|View full text |Cite
|
Sign up to set email alerts
|

Role of orf73 in the development of lambdoid bacteriophages during infection of the Escherichia coli host

Abstract: Shiga toxin-producing Escherichia coli (STEC) is a group of pathogenic strains responsible for human infections that result in bloody diarrhea and hemorrhagic colitis, often with severe complications. The main virulence factors of STEC are Shiga toxins encoded by stx genes located in genomes of Shiga toxin-converting bacteriophages (Stx phages). These bacterial viruses are clustered in the lambdoid bacteriophages family represented by phage λ. Here, we report that expression of orf73 from the exo-xis region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Gdansk). Throughout their studies, they have used four functional assays to assign the behavior of a given exo-xis gene as either pro-lysogenic or pro-lytic [ 24 , 25 , 26 , 27 ]. Two of the assays examine the time it takes for the lytic cycle to begin either from the onset of infection or the induction of lysogens by stressors such as hydrogen peroxide, antibiotics, and ultraviolet light.…”
Section: Conserved Genes Of the Exo-xis Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gdansk). Throughout their studies, they have used four functional assays to assign the behavior of a given exo-xis gene as either pro-lysogenic or pro-lytic [ 24 , 25 , 26 , 27 ]. Two of the assays examine the time it takes for the lytic cycle to begin either from the onset of infection or the induction of lysogens by stressors such as hydrogen peroxide, antibiotics, and ultraviolet light.…”
Section: Conserved Genes Of the Exo-xis Regionmentioning
confidence: 99%
“…From high-resolution cryo-EM studies, TraR alters the kinetics of promoter-bound RNAP at multiple stages ultimately inhibiting or stimulating transcription from the basal level [ 54 ]. In λ and Stx + phages, deletion of Orf73 resulted in lower survival rates upon infection and a lower efficiency of lysogenization both suggestive of a pro-lysogenic role during the phage developmental cycle [ 25 ]. Thus, as a TraR-like factor, Orf73 has the capacity to modify the expression of a wide repertoire of genes associated with the stress response through a direct interaction with RNAP [ 23 ].…”
Section: Structural Features Of the Conserved Exo-xis Region Proteinsmentioning
confidence: 99%
“…Stx phages share many characteristics with phage λ, a model system associated with many landmark discoveries in molecular biology. One shared genetic region found between the exo and xis genes encodes five proteins (Orf60a, Orf61, Orf63, Orf73, and Ea22) that may work separately or together at the earliest stages of infection to affect the commitment to a lysogenic or lytic developmental outcome [6][7][8] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Originally, exo-xis genes were associated with cell cycle and DNA replication changes driven by the p L promoter 9 during the earliest stages of infection with phage λ 10 . Assays that measure the period between induction and the observation of new viral progeny, the number of bacterial survivors after infection, and the efficiently in which bacteria are converted to lysogens all suggest that Orf60a, Orf61, and Orf63 are pro-lytic where Ea22 and Orf73 tend to be pro-lysogenic 8,11 . Orf63, the subject of this report, is a 63 amino acid protein that is highly conserved among λ and Stx phages alike 12 Since the effects of Orf63 and other exo-xis region gene products were amplified in STEC bacteria relative to benign E. coli strains infected with λ 13 , a closer examination may reveal new protein partnerships and pathways that Stx phages use to favor their success within their host.…”
Section: Introductionmentioning
confidence: 99%
“…The studies described briefly above indicated intriguing regulatory effects of the exo-xis region. However, despite further charactering principles of structures and basic functions of various products of genes from this region, like Ea8.5 (Kwan et al 2013 ), Orf63 (Dydecka et al 2017 ), Orf60a and Orf61 (Dydecka et al 2018 ), Orf73 (Zdrojewska et al 2019 ), and Ea22 (Dydecka et al 2020 ; Tong et al 2020 ), the role of the exo-xis region in modulating phage development and influencing host physiology remains unclear. Therefore, the aim of this work was to determine effects of the exo-xis region on development of the Stx phage Φ24 B and physiology and metabolism of its host.…”
Section: Introductionmentioning
confidence: 99%